Role of Knowledge Sharing , Transactional Leadership and Innovative Work Behavior in Tire Industry - Sumarsi, Sumarsi (Journal of Industrial Engineering & Management Research, 2019)
This study has three main purposes: first, to examine the effect of transactional leadership on knowledge sharing and innovative work behavior. Second, to examine the effect of knowledge sharing on innovative work behavior. Third, to examine the mediating role of knowledge sharing in the relationship between transactional leadership and innovative work behavior. The quantitative method is considered appropriate for this study, and a questionnaire is used to collect data from a total of 210 employees in Tire Industry who participated in the study. The SmartPLS-SEM version 3.0 is used to analyze data. The results reveal that transactional leadership has a positive and significant effect on knowledge sharing. However, transactional leadership directly has no significant effect on innovative work behavior. In addition, knowledge sharing positively and significantly affects innovative work behavior. This finding demonstrates that knowledge sharing becomes an essential mediator of transactional leadership and innovative work behavior in Tire Industry.